Plan de negocio para la creación de una empresa de fabricación y comercialización de calzado para mujeres embarazadas con plantillas de gel importadas desde Colombia - Armendáriz Lozada, María Belén (2018)
This document concentrates information regarding the possibility of generating a business related to an important industry in the country, this is the production of footwear, concentrated in an important segment of society, such as women who are in the gestation stage. To differentiate the footwear from the competition, it is used as the main input to gel insoles imported from Colombia. This product gives a special advantage to pregnant women due to its ability to provide comfort and allows a soft cushioning in contact with the floor, preventing inflammation of the legs and capillaries. Colombia has been chosen, because it is a country with a strong technology in the development of templates and materials for the production of shoes, which are one of the main products exported by that country, to this aspect should be added the commercial facility between the two countries. The brand that seeks to position in the market is Pettite Mere, which means small mom in French, in this way, a direct message is transmitted to the target market. The colors of the company seek to represent warmth as a mother does with her baby. In the financial field, the company plans to obtain a return on its initial investment from year 1, with the recovery threshold of the capital invested in year 4. The valuation of the project is positive because it has an internal rate of return higher than the rate discount calculated with market information, this allows to recommend its execution in the terms planned in the business plan.